The Effect of N-acetylcysteine on Periodontitis: A mini-review of literature (Research, Society and Development, 2021)
Recently, there is strong evidence for the beneficial role of antioxidants in the treatment of periodontal diseases. A drug that is gaining more and more focus in new research is N-acetylcysteine, an antioxidant that contributes to the increase in glutathione (GSH), used as a mucolytic agent, however, recent studies have shown its significant role in decreasing levels of reactive oxygen species and in the bone resorption process in experimental periodontitis, therefore, this review sought to elucidate whether N-acetylcysteine is effective in the treatment of periodontitis and also in the involved mechanisms already mentioned in the literature. The present study is a mini-review, in which a search was performed on Google Scholar, PubMed and Web of Science and databases for the collection of studies published in the last 10 years (2009-2020). The mini-review included studies that addressed a direct or indirect link between the effects of N-acetylcysteine on periodontitis, studies published in recent years, and in vitro and in vivo studies (animal and / or human models). Seven articles were selected from the following databases: PubMed (03) and Google Scholar (04) were subsequently analyzed. As for the language and the journal, all were published in international Journals and in English. It was concluded that N-acetylcysteine was effective in bone resorption in experimental periodontitis, but further studies are suggested in order to elucidate all the mechanisms involved in the observed results.